Study of the (n,2n) reaction cross section on 174,176Hf isotopes - Serris, M.; al., et (HNPS Advances in Nuclear Physics, 2020)
Cross section measurements of the 174Hf(n,2n)173Hf and 176Hf(n,2n)175Hf reactions have been performed at the VdG Tandem accelerator of NCSR “Demokritos” in Athens, in the neutron energy region from 8.8 to 11.5 MeV, using the activation technique. Statistical model calculations based on the Hauser - Feshbach theory have also been implemented by using the code EMPIRE-II with different sets of input parameters. The predictions were compared to the data of the present work as well as data from literature.